Economic Development of Tin Pewter Craftsmen in Pangkalpinang City, Bangka Belitung (2005–2015) - Ridha Albarokah; Farida R Wargadalem (Criksetra: Jurnal Pendidikan Sejarah, 2023)
Bangka Belitung Province is a producer of tin as a raw material for pewter crafts. The problem of this research is how is the economic development of pewter craftsmen in the city of Pangkalpinang (2005-2015)?. The aim of this research is to explain the economic development of Pewter craftsmen in Pangkalpinang City (2005-2015). The research uses historical research methods with steps namely heuristics, source criticism, interpretation and historiography. The results show that pewter crafts play a role in increasing the economy of the craftsmen. pewter 's craft has developed due to the support from PT Timah Tbk. Local governments also play an active role in marketing, as well as consumers. This craft gradually developed, along with the use of casting machine tools. The role of many parties and unique and high-quality products have attracted great demand from local, domestic and foreign consumers. Good marketing, provides benefits for entrepreneurs and pewter craftsmen, which in turn is able to increase the economy of the craftsmen. This research needs to be continued to find out further developments, and the obstacles they face in developing the typical crafts of the Bangka-Belitung Province.